Legal basis of the system of state support to the media (Herald of Journalism, 2018)
From the first days after the declaration of independence in the Republic of Kazakhstan for the establishment and development of a young independent state, one of the priority directions was the formation of the information space of the country and the support of domestic media for the protection of the domestic information market.One of the effective mechanisms of which was the state information order, that is, financial support of the mass media.State support for media is not a Kazakh innovation, but a practical mechanism for supporting mass media used in Western countries.The purpose of this study was to study the current situation in the field of public media financing in Kazakhstan and estimate the budget expenditures for a certain period.In recent years, we have seen an increase in the volume of public funding and an increase in the number of recipients of the information order.According to the PF “Legal Media Center” in the periodISSN 1563-0242 Herald of journalism. №2 (48). 2018 107ШурентaевА.М., ЕсдәулетовА.О.from 2009 to 2016, KZT 209.6 billion was allocated from the republican budget for information policyon improving the image of state bodies.In the conditions of the market and the proclamation of theopenness of the society, the distribution of government orders for the implementation of the informationpolicy should be open, which is not yet available in the system of state support for the media in Kazakhstan.In July 2017, on the website of the Ministry of Information and Communications of the Republic ofKazakhstan, a protocol was published of the results of the placement of the state order for conductingstate information policy at the republican level.However, the ministry refused to publish informationabout who received the budget funds totaling over two billion tenge.Now trials are underway.In this article, two opposing views are considered – supporting the state information order, on theone hand, and on the other hand, requiring open information in the allocation of the state budget.At thesame time, a comparative analysis of the legal foundations of the system of financial support of massmedia in Kazakhstan and foreign countries is given.Key words: governmental support, state information order, Media law, journalism, financing, right.